Submacular Injection of Ranibizumab as a New Surgical Treatment for Refractory Diabetic Macular Edema - Samir M. El-Baha; Ahmed M. Abdel Hadi; Mahmoud A. Abouhussein (Journal of Ophthalmology)
Purpose. In this study, we describe a new surgical technique for the treatment of refractory DME. The technique consists of vitrectomy with ILM peeling with a subretinal injection of ranibizumab. Methods. This is a prospective interventional noncomparative study including patients with refractory DME. Included patients were subjected to the new surgical technique of pars plana vitrectomy with subretinal injection of ranibizumab. Results. The study included 19 eyes with refractory macular edema, in which this novel technique was attempted. There were 10 males and 9 females. The age of the patients ranged from 17 to 67 years with a mean of 55.58 ± 13.242 years. The duration of diabetes before enrollment in the study ranged from 7 to 25 years with a mean of 16.3 years. Preoperatively, the mean CMT of the eyes ranged from 352 to 883 microns with mean ± SD of 498.58 ± 152.16 microns. Postoperatively, this improved significantly to 373.5 ± 100.3, 355.9 ± 89.8, and 365.74 ± 120.12 microns at 1, 3, and 6 months, respectively (p≤0.001 for all). Conclusion. This novel surgical procedure of vitrectomy with ILM peeling with a subretinal injection of ranibizumab is effective in cases of refractory DME. The study has been registered in Contact ClinicalTrials.gov PRS Identifier: NCT03975088.